STUDENTS’ VOCABULARY MASTERY ENHANCEMENT THROUGH CROSSWORD PUZZLE: CLASS ACTION RESEARCH IN A PUBLIC JUNIOR HIGH SCHOOL - Benny Nugraha; Marwito Wihadi (Universitas Widyatama, 2023)
Mastering vocabulary in English is such an essential facet that learners would be able to own productive and receptive skill needed to get their messages across and decipher the conveyed ones towards them. This Class Action Research (CAR) aims at pinpointing the intervention of Crossword Puzzle as a medium of teaching-learning vocabulary on Personal Recount Text. Collaborating with the classroom teacher, its use in one class of eight graded students in a public junior high school in West Java is conducted together with the instruments of observation and tests. It is found out that Crossword Puzzle radiates the teaching-learning process positively on account of students’ enthusiasm and responses as well as profoundly inclines the mean of Pre-test, 40.61 to the one of Post-test, 80.60 aside from the majority of the students’ achievement to the success indicator score on vocabulary mastery in one Cycle. Despite its benefits to other parties, it is advisable that further research is to fill the gaps on other writing genre with discrepant learning contexts.